Carpal Tunnel Syndrome and Calcium Deposit in the Surgically Transacted Transverse Carpal Ligament - Ali Abbas Hashim Al-Musawi; Nadia Mahmoud Tawfiq Jebril; Amer Abbas. H. AL-Auhaimid; Zaid Hadi. K. Hammoodi (The Scientific World Journal)
A diagnosis of carpal tunnel syndrome (CTS) in a human often contains more than one test. Calcification of the traverse carpal ligament (TCL) is the common reason why patients seek CTS surgery. However, the determination of calcium (Ca) concentration in the TCL has not been studied. The results of environmental toxicity studies assessing the relationship between Ca and elemental deposition in the TCL are inconsistent. The purpose of this paper was to verify this hypothesis by conducting a chemical analysis of a portion of the released TCL to assess whether there is a relationship between CTS and Ca, measured as the total concentration of Ca, and to measure the precipitation of elements; the most closely related elements associated with Ca are cadmium and lead, which are also toxic. Surgical release of TCL was performed on forty patients. Total concentrations of Ca, Cd, and Pb in the extracted portion of TCL were digested and determined using inductively coupled plasma mass spectrometry (ICP-MS) and the possibility of using X-ray spectroscopy (XRF) for direct elemental analysis. Ca mineralisation was revealed in some TCLs. In assessing patients’ environmental pollution, it was observed that the Cd and Pb concentrations were significant with a higher Ca concentration, and XRF was useful for direct detection of the elements in samples of the human body. These results indicate that TCL mineralisation by Ca does not characterise CTS, which has important concerns in improving patients’ therapeutic strategies, and Cd and Pb concentrations varied due to different factors.